A Pollen Record Of Alluvium Unit And Vegetation Landscape From Bangka Island, Indonesia - Sri Sukapti, Woro; Yulianto, Eko; Kurnia; Suharsono (Pusat Survei Geologi, 2025)
This study presents a pollen record of the purported Holocene Alluvium in Bangka Island, Indonesia. This alluvial unit’s age and stratigraphic position have been disputed, and this pollen study is expected to provide crucial evidence on the matter. The pollen content is also likely to reveal the vegetation landscape and environment of the samples, further enhancing our understanding of the area. Three samples were taken from outcrops at three different points of the alluvial deposit, and the samples were rich in pollen and spores. We identified 54 pollen and 12 spore taxa. The pollen assemblages suggest that the samples were deposited in an open forest environment of the evolving disturbed heath forest ecosystem. Several cultivated plant pollens indicate that the samples were deposited in modern times. Keywords: Holocene, alluvium, stratigraphy, pollen, Bangka, vegetation landscape Keywords: Holocene, alluvium, stratigraphy, pollen, Bangka, vegetation landscape